2010
DOI: 10.1111/j.1365-2141.2010.08235.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance treatment with azacytidine for patients with high‐risk myelodysplastic syndromes (MDS) or acute myeloid leukaemia following MDS in complete remission after induction chemotherapy

Abstract: SummaryThis prospective Phase II study is the first to assess the feasibility and efficacy of maintenance 5-azacytidine for older patients with high-risk myelodysplastic syndrome (MDS), chronic myelomonocytic leukaemia and MDS-acute myeloid leukaemia syndromes in complete remission (CR) after induction chemotherapy. Sixty patients were enrolled and treated by standard induction chemotherapy. Patients that reached CR started maintenance therapy with subcutaneous azacytidine, 5/28 d until relapse. Promoter-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 41 publications
3
49
0
1
Order By: Relevance
“…These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21. Importantly, the study of azacitidine has revealed nuances of treatment with DNMTi therapy not seen with the use of traditional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21. Importantly, the study of azacitidine has revealed nuances of treatment with DNMTi therapy not seen with the use of traditional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Grade III-IV thrombocytopenia and neutropenia occurred after 9.5 and 30% of the cycles, respectively, while haemoglobin levels increased during treatment. azacitidine treatment is safe, feasible and may be of benefit in a subset of patients (Grövdal et al, 2010). It has been studied predominantly in higher-risk MDS patients.…”
Section: Azacitidine For Maintenance Of Complete Remission After Chemmentioning
confidence: 99%
“…The EPO dose required is 40.000-60.000 units 1-3 times a week subcutaneously. Erythroid response occur within 6 to 8 weeks of treatment (Hellström-Lindberg E, 2003;Jädersten et al, 2008). In a phase 3 prospective randomized trial the efficacy and long-term safety of EPO with or without granulocyte colony-stimulating factor plus supportive care was evaluated versus supportive care alone for the treatment of anaemic patients with lower-risk MDS ).…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%
“…46 Further development of the treatment paradigm has suggested that less toxic regimens (lower doses with more frequent dosing) and the use of maintenance DMNT inhibitors as adjunct therapy or in combination with other novel therapies such as lenalidomide may be effective in subsets of patients with high-risk MDS/AML. [47][48][49] DNA hydroxy-methylation and the TET enzymes Though DNA methylation was initially believed to be a relatively stable DNA modification, genome-wide high resolution mapping of 5mC during cellular differentiation and the recent identification of the Ten-Eleven-Translocation (TET) enzymes has revealed a more dynamic state of affairs. 15,50,51 The three TET enzymes (TET1-3) are α-ketoglutarate (α-KG) and Fe 2+ -dependent dioxygenase enzymes, which catalyze the successive oxidation of 5mC to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine and 5-carboxycytosine.…”
Section: Dna Methylation As a Therapeutic Target In Myeloid Malignanciesmentioning
confidence: 99%